2021
DOI: 10.1055/s-0041-1740928
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Outcomes of Total Knee Arthroplasty in Sarcopenia: A Case–Control Retrospective Cohort Study

Abstract: Background The aim of the study was to investigate the relationship between sarcopenia and both clinical and functional outcome scores following total knee arthroplasty (TKA) performed for patients over 65 years of age. Methods We assessed patient demographics, preoperative health status, postoperative Knee Society Clinical (KSS-C) and Function (KSS-F) subscores, and perioperative complications for 180 patients with sarcopenia and 345 comparatively healthy patients at a mean of 12.0 months after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 22 publications
2
7
2
Order By: Relevance
“…29 In addition, He et al demonstrated that the sarcopenia group had a higher blood transfusion rate than the non-sarcopenia group in patients undergoing TKA. 12 The discrepancies between our findings and previous studies could be attributed to the use of the ERAS protocol.…”
Section: Total Estimated Blood Loss and Blood Transfusioncontrasting
confidence: 98%
See 3 more Smart Citations
“…29 In addition, He et al demonstrated that the sarcopenia group had a higher blood transfusion rate than the non-sarcopenia group in patients undergoing TKA. 12 The discrepancies between our findings and previous studies could be attributed to the use of the ERAS protocol.…”
Section: Total Estimated Blood Loss and Blood Transfusioncontrasting
confidence: 98%
“…11 He et al reported that patients with sarcopenia who underwent TKA had increased postoperative complication rates, such as nausea, vomiting, edema of the operated limb and deep vein thrombosis, compared to the healthy control group. 12 These results were generally in line with our findings. Compared with those in the non-sarcopenia group, patients with sarcopenia had higher surgical complication rates after TKA in this study.…”
Section: Postoperative Complicationssupporting
confidence: 92%
See 2 more Smart Citations
“…The non-parametric Mann–Whitney test was used for the comparison between the two groups for the variables “Disease Index” and “Waist/heel ratio”. Two-way repeated measures analysis of variance (ANOVA) was performed to compare the mean values of the dependent variable KOOS between the two groups (non-sarcopenic and sarcopenic) before and after surgery (main effects and interaction), as previously described [ 40 ]. Results are presented as mean ± standard deviation, and the level of statistical significance was set at the p < 0.05 level.…”
Section: Methodsmentioning
confidence: 99%